Use of Ancient Sedimentary DNA as a Novel Conservation Tool for High‐Altitude Tropical Biodiversity. Issue 2 (26th December 2013) - BOESSENKOOL, SANNE; MCGLYNN, GAYLE; EPP, LAURA S.; TAYLOR, DAVID; PIMENTEL, MANUEL; GIZAW, ABEL; NEMOMISSA, SILESHI; BROCHMANN, CHRISTIAN; POPP, MAGNUS
Abstract Conservation of biodiversity may in the future increasingly depend upon the availability of scientific information to set suitable restoration targets. In traditional paleoecology, sediment‐based pollen provides a means to define preanthropogenic impact conditions, but problems in establishing the exact provenance and ecologically meaningful levels of taxonomic resolution of the evidence are limiting. We explored the extent to which the use of sedimentary ancient DNA (sedaDNA) may complement pollen data in reconstructing past alpine environments in the tropics. We constructed a record of afro‐alpine plants retrieved from DNA preserved in sediment cores from 2 volcanic crater sites in the Albertine Rift, eastern Africa. The record extended well beyond the onset of substantial anthropogenic effects on tropical mountains. To ensure high‐quality taxonomic inference from the sedaDNA sequences, we built an extensive DNA reference library covering the majority of the afro‐alpine flora, by sequencing DNA from taxonomically verified specimens. Comparisons with pollen records from the same sediment cores showed that plant diversity recovered with sedaDNA improved vegetation reconstructions based on pollen records by revealing both additional taxa and providing increased taxonomic resolution. Furthermore, combining the 2 measures assisted in distinguishing vegetation change at different geographic scales; sedaDNA almost exclusively reflects local vegetation, whereas pollen can potentially originate from a wide area that in highlands in particular can span several ecozones. Our results suggest that sedaDNA may provide information on restoration targets and the nature and magnitude of human‐induced environmental changes, including in high conservation priority, biodiversity hotspots, where understanding of preanthropogenic impact (or reference) conditions is highly limited. Uso de ADN Sedimentario Antiguo como una Herramienta Novedosa de Conservación para la Biodiversidad Tropical de Grandes Altitudes